Application of Methylamine Gas in Fabricating Organic–Inorganic Hybrid Perovskite Solar Cells. Issue 10 (14th September 2017) - Raga, Sonia R.; Jiang, Yan; Ono, Luis K.; Qi, Yabing
Abstract: Since a hybrid perovskite‐based solar cell was reported for the first time, its efficiency and stability were boosted to remarkably high levels. With record efficiencies beyond 22 % and record stability up to 10 000 h under working conditions, perovskite solar cells are a promising candidate for further commercial applications. Among the myriads of fabrication methods to deposit perovskite films, we have chosen a unique technique that only needs methylamine gas (CH3 NH2 ) to convert the inorganic film. In contrast to all other fabrication methods, this is based on room temperature and exposure to an organic gas exposure at ambient pressure, which can be easily employed for large‐area and fast coatings. In this Review, the advantages and characteristics of methylamine gas applications will be discussed. First, we will evaluate the different techniques to convert an inorganic film into a perovskite with an emphasis on the chemical interactions. Then, we will summarize the applications of methylamine gas to "heal" and improve the perovskite films prepared by other methods. Abstract : MAGIC, or methylamine gas‐induced conversion of perovskite is a very versatile technique for solar‐cell fabrication. It can rapidly form high‐quality perovskite films by exposing lead halide precursors to methylamine gas and can improve the morphology and electrical properties of perovskite layers by short exposures. Ultra‐smooth and pinhole‐free films over large areas can be easily fabricated with methylamine gas.